2023
DOI: 10.2147/jmdh.s394396
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Family Functioning and Health Beliefs in Patients with Stroke in Beijing, China

Abstract: Objective To explore the relationship between family functioning and health beliefs in patients with stroke. Methods A total of 253 patients with stroke were selected from Beijing Luhe Hospital, Capital Medical University from May 2021 to November 2021. All patients were of Chinese nationality, and 240 valid questionnaires were obtained. The Family Assessment Device and Champion’s Health Belief Model Scale were used to collect patients’ family functioning and health bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…A review (53) summarized the performance of the Chinese version of the Family Assessment Device and found that it has shown good reliability and validity in Chinese participants since its validation. This scale also achieved high reliability (0.79-0.92) in recent studies using Chinese adult samples (54,55). In this study, Cronbach's alpha for this device was 0.88.…”
Section: Family Functionsupporting
confidence: 58%
“…A review (53) summarized the performance of the Chinese version of the Family Assessment Device and found that it has shown good reliability and validity in Chinese participants since its validation. This scale also achieved high reliability (0.79-0.92) in recent studies using Chinese adult samples (54,55). In this study, Cronbach's alpha for this device was 0.88.…”
Section: Family Functionsupporting
confidence: 58%
“…Conversely, if family members can engage in good affection interaction and positive communication, uphold altruism, solve problems, and adjust family rules, the unhealthy perception and belief in pain, such as pain catastrophizing, can be avoided. This is probably because good family functioning can enhance the patient's confidence in overcoming the disease and make them more proactive in responding to pain (Zhang et al, 2023; Zhou et al, 2023). Of note, approximately half of the participants in this study had clinically significant pain catastrophizing.…”
Section: Discussionmentioning
confidence: 99%